Implementasi Pendekatan Humanistik Pada Proses Pembelajaran Matematika dan Dampaknya Terhadap Motivasi Belajar di Sekolah Dasar - Kosasih, Lenny (Jurnal PGMI UNIGA, 2025)
Learning mathematics is a mental activity that involves understanding the meaning of relationships and symbols and then applying them to real-life situations. Conventional methods have proven to be ineffective in improving students' understanding, so a humanistic approach to mathematics learning is needed. This study aims to analyze the humanistic approach implemented in mathematics learning and its impact on students' learning motivation in elementary schools. There are similarities between mathematics learning and the humanistic approach, both of which emphasize the importance of respecting each individual in relationships and symbols that will be applied in real life. This study uses a descriptive research design through a case study approach. The researcher aims to increase the motivation, interest, and learning outcomes that result from using a humanistic approach to learning mathematics. Observations were made in relation to the planning, implementation, and evaluation of the learning process, and data collection techniques included various methods such as observation, interviews, and performance. The research subjects consisted of 20 sixth grade students at SDN Batujajar 1, including 10 male students and 10 female students in the academic year 2024/2025. The results of the study indicate that the application of the humanistic approach in mathematics learning has a positive impact on students' motivation, interest, and learning outcomes. Keywords: Humanistic approach, learning mathematics, learning motivation